Cruzipain promotes Trypanosoma cruzi adhesion to Rhodnius prolixus midgut. - Lívia Almeida Uehara; Otacílio C Moreira; Ana Carolina Oliveira; Patrícia Azambuja; Ana Paula Cabral Araujo Lima; Constança Britto; André Luis Souza dos Santos; Marta Helena Branquinha; Claudia Masini d'Avila-Levy (Public Library of Science (PLoS), 2012)
BACKGROUND:Trypanosoma cruzi is the etiological agent of Chagas' disease. Cysteine peptidases are relevant to several aspects of the T. cruzi life cycle and are implicated in parasite-mammalian host relationships. However, little is known about the factors that contribute to the parasite-insect host interaction. METHODOLOGY/PRINCIPAL FINDINGS:Here, we have investigated whether cruzipain could be involved in the interaction of T. cruzi with the invertebrate host. We analyzed the effect of treatment of T. cruzi epimastigotes with anti-cruzipain antibodies or with a panel of cysteine peptidase inhibitors (cystatin, antipain, E-64, leupeptin, iodocetamide or CA-074-OMe) on parasite adhesion to Rhodnius prolixus posterior midgut ex vivo. All treatments, with the exception of CA074-OMe, significantly decreased parasite adhesion to R. prolixus midgut. Cystatin presented a dose-dependent reduction on the adhesion. Comparison of the adhesion rate among several T. cruzi isolates revealed that the G isolate, which naturally possesses low levels of active cruzipain, adhered to a lesser extent in comparison to Dm28c, Y and CL Brener isolates. Transgenic epimastigotes overexpressing an endogenous cruzipain inhibitor (pCHAG), chagasin, and that have reduced levels of active cruzipain adhered to the insect gut 73% less than the wild-type parasites. The adhesion of pCHAG parasites was partially restored by the addition of exogenous cruzipain. In vivo colonization experiments revealed low levels of pCHAG parasites in comparison to wild-type. Parasites isolated after passage in the insect presented a drastic enhancement in the expression of surface cruzipain. CONCLUSIONS/SIGNIFICANCE:These data highlight, for the first time, that cruzipain contributes to the interaction of T. cruzi with the insect host.